Aflatoxin metabolism in humans: detection of metabolites and nucleic acid adducts in urine by affinity chromatography. - Groopman, J D (1985)
A high-affinity IgM monoclonal antibody specific for aflatoxins was covalently bound to Sepharose 4B and used as a preparative column to isolate aflatoxin derivatives from the urine of people and experimental animals who had been exposed to the carcinogen environmentally or under laboratory conditions. Aflatoxin levels were quantified by radioimmunoassay and high-performance liquid chromatography after elution from the affinity column. In studies on rats injected with [14C]aflatoxin B1, we identified the major aflatoxin-DNA adduct, 2,3-dihydro-2-(N7-guanyl)-3-hydroxy-aflatoxin B1 (AFB1-N7-Gua), and the oxidative metabolites M1 and P1 as the major aflatoxin species present in the urine. When this methodology was applied to human urine samples obtained from people from the Guangxi Province of China exposed to aflatoxin B1 through dietary contamination, the aflatoxin metabolites detected were also AFB1-N7-Gua and aflatoxins M1 and P1. Therefore, affinity chromatography using a monoclonal antibody represents a useful and rapid technique with which to isolate this carcinogen and its metabolites in biochemical epidemiology and for subsequent quantitative measurements, providing exposure information that can be used for risk assessment.